The Independency of Elle Evans Trough Plot in “Kissing Booth 3” Movie - Ni Putu Nanda Pridayanti; I Wayan Juniartha , I Wayan Juniartha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The aim of this study is to find out the freedom expression, the thoughts of the main character, Elle Evans in “The Kissing Booth 3” Movie. The data source comes from “The Kissing Booth 3” movie, the form of the data is in the form of Elle Evans dialogue. The method used in collecting the data is observation method such as download movie, watching with English subtitles, taking note the data obtained, and classifying.. This data analysis method uses a qualitative descriptive method using the theory of Gustav Freytag (1990). The results of this analysis are exposition, rising action, climax, falling action, and catastrophe found in “The Kissing Booth 3” movie. All of these terms have been categorized into their respective groups.